Boosting Coulombic Efficiency of Conversion‐Reaction Anodes for Potassium‐Ion Batteries via Confinement Effect. (30th October 2020) - Cao, Kangzhe; Zheng, Runtian; Wang, Shaodan; Shu, Jie; Liu, Xiaogang; Liu, Huiqiao; Huang, Ke‐Jing; Jing, Qiang‐Shan; Jiao, Lifang
Abstract: Potassium‐ion battery anode materials with high capacity always hold one or more K ions and are companied by large volume swelling, which threatens the stability of solid‐electrolyte‐interface (SEI) layers, and results in low coulombic efficiency as well as inferior cycling stability. Herein, an avenue that induces the rapid formation of continuous SEI layers by the confinement effect to boost K ions storage property is proposed. CuS nanoplates are dispersed on the core layer of carbon nanofibers and further confined by the Nb2 O5 ‐C shell layer, constructing core–shell structure CuS‐C@Nb2 O5 ‐C nanofibers (NFs). The shell layer protects the CuS nanoplates from immediate contact with the electrolyte and brings about volume expansion, assisting the rapid formation of continuous SEI layers. As a result, the capacity retention of the CuS‐C@Nb2 O5 ‐C NFs electrode remains at 93.1% after 100 cycles, much larger than that of the CuS‐C NF electrode (74.6%); the process that coulombic efficiency stabilized above 99.0% shortens to 5 cycles from 30 cycles. This progress is also found in the CoS2 ‐C@Nb2 O5 ‐C and NiS2 ‐C@Nb2 O5 ‐C NFs electrodes. The improved coulombic efficiency and cycling stability brought about by the confinement effect offer a facile approach to boost the K ion storage property of conversion reaction anodes. Abstract : The confinement effect is employed to boost the coulombic efficiency and cycling stability of potassium‐ion battery anodes. Taking CuS as a proof of conversion reaction electrode material, volume expansion is restrained and continuous solid‐electrolyte‐interface layers are constructed rapidly in the designed CuS‐C@@Nb2 O5 ‐C nanofibers electrode, which provides a neat approach to improve the K ion storage property of conversion reaction anodes.